Antiglycemic Effect of Water Extractable Arabinoxylan from Wheat Aleurone and Bran - Lovemore Nkhata Malunga; Marta Izydorczyk; Trust Beta (Journal of Nutrition and Metabolism)
The studies on the effects of arabinoxylan (AX) polysaccharides on postprandial glucose response have resulted in contrasting results owing to the diversity in AX structures. Four water extractable AX (WEAX) extracts obtained from wheat aleurone and bran were used to investigate (a) the effect of AX on activities of α-amylase and α-glucosidase, (b) influence of AX chemical composition on their inhibition potency, and (c) kinetics of enzyme inhibition. α-Amylase activity was not significantly affected by the presence WEAX fractions regardless of type or concentration. WEAX inhibited α-glucosidase activity only when maltose was used as a substrate but not sucrose. The IC50 values of WEAX (4.88±0.3–10.14±0.5 mg/mL) were highly correlated to ferulic acid content (R=-0.89), arabinose to xylose ratio (R=-0.67), and relative proportions of xylose being unsubstituted (R=0.69), disubstituted (R=-0.63), and monosubstituted (R=-0.76). The Lineweaver–Burk plot suggested an uncompetitive enzyme inhibition mode. Thus, our results suggest that antiglycemic properties of WEAX may be derived from direct inhibition of α-glucosidase activity.